2020
DOI: 10.1371/journal.pgen.1009114
|View full text |Cite
|
Sign up to set email alerts
|

Selection of GmSWEET39 for oil and protein improvement in soybean

Abstract: Soybean [Glycine max (L.) Merr.] was domesticated from wild soybean (G. soja Sieb. and Zucc.) and has been further improved as a dual-use seed crop to provide highly valuable oil and protein for food, feed, and industrial applications. However, the underlying genetic and molecular basis remains less understood. Having combined high-confidence bi-parental linkage mapping with high-resolution association analysis based on 631 whole sequenced genomes, we mapped major soybean protein and oil QTLs on chromosome15 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 47 publications
1
56
1
Order By: Relevance
“…The phenotypic value of each seed trait analyzed in the study is the accumulative effect of their QTLs across the soybean genome. Multiple causal genes for each seed trait including SWEET10a (also named as SWEET39 ) underlying a major protein and oil QTL have been identified 42 44 . The interaction of POWR1 with other QTLs that determine the phenotypic value of the seed traits, however, are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic value of each seed trait analyzed in the study is the accumulative effect of their QTLs across the soybean genome. Multiple causal genes for each seed trait including SWEET10a (also named as SWEET39 ) underlying a major protein and oil QTL have been identified 42 44 . The interaction of POWR1 with other QTLs that determine the phenotypic value of the seed traits, however, are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The location of this QTL was subsequently narrowed to 8.4 Mb [162], <1 MB [163], 77.4 kb [137], and even with only three candidate genes [131] on LG20. Likewise, another major SPC QTL, qSeedPro_15, was narrowed to 4 Mb (Zhang et al [164]; see Table 3), overlapping the previously identified genomic region on chromosome 15 [24,131,155,165,166]. Zhang et al [164] elucidated a possible candidate gene Glyma.15G049200 underlying the QTL.…”
Section: Qtl Mapping For Seed Protein Contentmentioning
confidence: 85%
“…The authors also elucidated eight novel genomic regions controlling methionine, cysteine, lysine, and threonine contents. A GWAS using whole genome sequencing data of 631 soybean accessions combined with a biparental QTL analysis uncovered a pleotropic gene GmSWEET39 (encoding sugar transporter) controlling SPC and seed oil content in soybean [ 164 ]. The authors also reported that a 2 bp (CC) deletion in Glyma.15G049200 underlying the GmSWEET39 allele rendered high seed oil content and low SPC.…”
Section: Underpinning Genomic Region/haplotypes Controlling High Prot...mentioning
confidence: 99%
See 1 more Smart Citation
“…GmSWEET15 mediated sucrose export from endosperm to early embryo (Wang et al ., 2019d). GmSWEET10a and GmSWEET10b determined oil and protein contents and seed size simultaneously in soybean through affecting sugar allocation from seed coat to embryo (Miao et al ., 2020; Wang et al ., 2020e; Zhang et al ., 2020c).…”
Section: Genes Responsible For Important Agronomic Traitsmentioning
confidence: 99%